A LOOK AT SALES AND EMAIL MARKETING PERSONALIZATION WITH ARTIFICIAL INTELLIGENCE - Nelo, Victor Hugo Amador; Carrino, Adauto Luiz (Seven Editora, 2025)
This study investigates how Artificial Intelligence (AI) applied to email marketing personalization impacts sales and customer engagement. The research, of a qualitative nature, is based on bibliographic analyses and recent studies on the use of AI in digital marketing. The results show that the technology enables large-scale personalization, allowing messages to be segmented according to consumer behavior and preferences. This approach increases open, click, and conversion rates while strengthening the relationship between brands and customers. It was also observed that intelligent automation optimizes the time and resources of marketing teams, making campaigns more efficient and profitable. However, challenges related to implementation costs and the need for qualified professionals were identified. It is concluded that integrating AI into email marketing represents a competitive advantage, enabling more personalized, strategic, and humanized communications that enhance commercial performance in the digital environment. DOI: https://doi.org/10.56238/sevened2025.029-120